The effect of some excipients on the formulation of norfloxacin 400mg tablets - Al-Khalidi S. Siham (College of Pharmacy / Mustansiriyah University, 2004)
Norfloxacin a synthetic, broad-spectrum quinolone carboxylic acid derivative, active against Gram negative & Gram-positive bacteria. Used clinically in the treatment of acute and chronic urinary tract infections, cystitis ,urethritis, pyelonephritis, prostatitis& gastroenteritis . This study is concerned with the formulation of 400mg Norfloxacin coated tablets with 710mg weight, 12mm in diameter, less than 10minutes disintegration time, & less than 1 % friability. Many trials were made to prepare a satisfactory tablet formula for the drug by using wet-granulation method with various additives. It was found that Polyvinylpyrrolidone as a binder gives the most satisfactory tablets. The effect of disintegrants on drug release was also investigated on the selected formulas. Conventional corn starch, sodium starch glycolate and microcrystalline cellulose were tried as disintegrants. It was found that cross-caramellose (carboxymethylcellulose) was the best disintegrants. A comparative study on the physical properties of the prepared tablets with Noroxacine ( Razi labs,Aleppo.Syria ) , Neofloxacin ( the Alexandria. Egypt ), and Norfloxacin showed that the release of the drug from the selected formula was similar to that obtained from Alexandria. The stability of the prepared tablets was studied at 25°C, 40°C, 50°C, &70°C and the expiration date was calculated and found to be equal to 7.3 years, 4.7 years, and 2.4 years & four months respectively. Key word: Norfloxacin- Pharmacokinetics.Fluoroquinolone- Norfloxacin formulation.